Cross This Out: A Pedagogy of Disruption and Healing - Reyes, G.T. (Radical Teacher, 2019)
Critical courage and love require that we consider our own humanity's need for not only justice but also healing. Often, radical educators relentlessly focus on working towards social justice to the point where they neglect their own self-preservation, which includes processes and practices of healing. This article discusses how a pedagogy of disruption and healing were applied towards confronting a racist act of vandalism at a California public university. In discussing the values-centered, socio-historically grounded, and higher purpose-driven responses to the racist act, the author illuminates the four principles that grounded the disruptive and healing-centered actions. In making transparent the principles that informed the designed response, others can be able to make adaptations necessary for their own contexts. To assist with invoking one’s radical agency the author also reveals how other educators across the country have implemented these principles within their own contexts towards manifesting their own visions of a more healthy, just, and meaningful life that is rooted in an analysis of the conditions that inhibit that well-being in the first place.